CO2 Reduction Measures in Steam Cracker Plants: Process integration opportunities of electrified steam methane reforming for fuel gas valorization - Lehle, Tobias (My University, 2022)
Steam cracking is the main production route for the light olefins ethylene and propylene, which are considered a cornerstone of the chemical industry. The endothermic cracking reactions are conventionally supplied with heat by combusting fossil fuel and therefore entail large carbon dioxide emissions. Typically the fuel grade byproducts methane and hydrogen are used as fuel gas. Possible options to decarbonize the process include either the substitution of fossil feedstock, by e.g. biomass or recycled waste, or the heat supply to the reactions. While the industry strives for electrification of the cracker to decarbonize the heat supply, using hydrogen as fuel gas is a readily available decarbonization measure. To obtain hydrogen, the co-produced methane can be reformed. This work modelled the integration of an electrified steam methane reformer with an ethane steam cracker. The emission reduction potential and impact on the energy balance of an ethane cracker of two emission reduction scenarios was analysed. One scenario is categorized as pre-combustion carbon capture, while the other uses oxy-fuel combustion to reduce emissions. It was shown that both scenarios allow significant emission reduction of approximately 95 %, where the residual emissions steam from electricity consumption assuming Sweden’s carbon grid intensity. The modeled scenarios showed that usage of reformed hydrogen for combustion entails a lower increase (1.1 MJ/kgEthylene) in specific energy consumption than oxy-fuel combustion (1.7-2.4 MJ/kgEthylene).
Keywords: Steam Cracking; CO2 Reduction; Steam Reformation; e-SMR; Methane Valorization; Fuel Switching; Pre-combustion; Oxy-fuel Combustion